The Political Empowerment of Village Women Through The Mushroom House Entrepreneurship Program In Kramattemenggung Village - Hikmah Muhaimin; Ahmad Hasan Afandi; Jenny Yudha Utama; Ayunda Eka Permata; Nur Alifa (Journal of Contemporary Local Politics, 2026)
- Village women's empowerment is an important strategy to encourage inclusive and sustainable village development because village women have great potential in strengthening the family economy and social development, but their involvement is often not optimal. The research conducted aims to analyze the role of the village government to support the empowerment of village women through the mushroom house entrepreneurship program in Kramattemenggung Village with a descriptive qualitative method using in-depth interview data collection techniques, observation, and documentation. The research informants included village government officials, program managers, and village women involved in the mushroom house program. The research indicates that the village government plays a role as a facilitator and driver in the implementation of the mushroom house entrepreneurship program through program planning, administrative support, and the creation of participation spaces for village women. This program has a positive impact on the empowerment of village women as shown through capacity building, open access to economic resources, and increased women's participation in village entrepreneurship activities. This finding is the same as the theory of community empowerment according to Edi Suharto, which views empowerment as a process of increasing capacity, access, and community participation in development. Therefore, this study concludes that the mushroom house entrepreneurship program can be a relevant and sustainable model of village women's empowerment if supported by the active role of the village government and the direct involvement of women as the main actors of village economic development.